2004
DOI: 10.5194/acp-4-2313-2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of archived and off-line diagnosed vertical diffusion coefficients from ERA-40 with <sup>222</sup>Rn simulations

Abstract: Abstract. Boundary layer turbulence has a profound influence on the distribution of tracers with sources or sinks at the surface. The 40-year ERA-40 meteorological data set of the European Centre for Medium-range Weather Forecasts contains archived vertical diffusion coefficients. We evaluated the use of these archived diffusion coefficients versus off-line diagnosed coefficients based on other meteorological parameters archived during ERA-40 by examining the influence on the distribution of the radionuclide 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, this requires the fluxes to be known at least as well as we already have knowledge about the fluxes targeted in the inversion. Given the prior knowledge of CO 2 fluxes and their spatial and temporal patterns, and given the problems in properly simulating the emanation rate of 222 Rn (Olivié et al, 2004), we see only limited potential in this tracer. For SF 6 , the location and strength of local emissions are often dominating variability of measurements in the continental boundary layer (Rivier et al, 2006).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…However, this requires the fluxes to be known at least as well as we already have knowledge about the fluxes targeted in the inversion. Given the prior knowledge of CO 2 fluxes and their spatial and temporal patterns, and given the problems in properly simulating the emanation rate of 222 Rn (Olivié et al, 2004), we see only limited potential in this tracer. For SF 6 , the location and strength of local emissions are often dominating variability of measurements in the continental boundary layer (Rivier et al, 2006).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Vertical diffusion of tracers in TM5 is described with a first-order closure scheme, where the diffusion coefficient is assumed to be the same as for heat (Olivié et al, 2004a). In the free troposphere it is computed based on wind shear and static stability following Louis (1979).…”
Section: Transportmentioning
confidence: 99%
“…It has been shown that vertical diffusion has significant impacts on simulated chemical concentrations (e.g. Oliviè et al 2004;Nowacki et al 1996;Biswas and Rao 2000). On the other hand, the evaluation of K (z) is not an easy task because the diffusion coefficients cannot be measured directly, and their numerical representations are only a simplification of complex physical processes (e.g.…”
Section: Introductionmentioning
confidence: 99%